Asuransi Syariah dalam Menopang Pemulihan Ekonomi Berdasarkan Undang-Undang Nomor 40 Tahun 2014 Tentang Perasuransian - Karso, A. Junaedi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
In Indonesia, there is unit-linked sharia insurance. The governance of Islamic financial instruments tends to be considered better than conventional instruments. The sharia principle is the principle of Islamic law in insurance activities based on fatwas issued by institutions that have authority in determining fatwas in the field of sharia. Based on Law Number 40 of 2014, sharia insurance is a collection of agreements, consisting of agreements between sharia insurance companies (tijarah or buying and selling contracts) and policyholders as well as agreements between policyholders (tabarru' or social funds), in the context of contribution management. The basic principle of Islamic finance is that the economy of the people involves the participation of as many people as possible.